Juridical Analysis of Judgment Number 03/Pid.Sus-Anak/2020/PN.Enr in Light of Law Number 1 of 2023 on the Criminal Code and Law Number 11 of 2012 on the Juvenile Criminal Justice System - Muhammad Rizky Ramadhani; Abraham Ferry Rosando (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the legal considerations underlying the imposition of imprisonment and vocational training on a juvenile offender in Judgment Number 03/Pid.Sus-Anak/2020/PN.Enr and evaluates its conformity with Law No. 11 of 2012 concerning the Juvenile Criminal Justice System and Law No. 1 of 2023 concerning the Criminal Code. The research employs a normative juridical method using statutory and case approaches. Primary legal materials consist of relevant legislation and the court judgment, while secondary legal materials include legal literature and scholarly publications on juvenile criminal law and restorative justice. The collected legal materials are analyzed qualitatively through legal interpretation and doctrinal analysis. The findings indicate that the court considered both juridical and non-juridical factors, including the seriousness of the offense, the child's personal circumstances, and the objectives of juvenile justice. The imposition of imprisonment was intended to ensure accountability for a serious violent offense resulting in death, whereas vocational training functioned as a rehabilitative measure to promote the child's personal development and social reintegration. Although diversion was not applicable due to the gravity of the offense, the judgment reflects the principles of restorative justice by emphasizing rehabilitation alongside punishment. Furthermore, the court's reasoning is consistent with the sentencing philosophy embodied in Law No. 1 of 2023, which promotes proportionality, rehabilitation, and the restoration of social balance. Accordingly, the combination of imprisonment and vocational training demonstrates a balanced approach that protects the interests of victims while safeguarding the rights and future development of juvenile offenders.